Judicialization of politics in Indonesia’s electoral system Case study: judicial review on threshold, balloting structure, and simultaneous election at constitutional court - Pratama, Heroik Mutaqin; Perdana, Aditya (Political Science Program, Universitas Negeri Semarang, 2021)
Why does the judicial review process highly influence the electoral system design in Indonesia at the Constitutional Court? Whose interests and what kind of interests are served by the judicial review process at the Constitutional Court towards the electoral system in Indonesia? By analyzing constitutional court verdicts from its inception on August 13, 2003, until the beginning of 2020, this study tries to answer those two questions by using judicialization of political theory. This study found that the extension of the authority of the judicial institution to produce political decisions through the judicial review mechanism can be regarded as the opening of political opportunity structure as a new platform for political actors to achieve their interest in election regulations. For example, to meet one of the electoral systems, a political party is underwhelming variables like the parliamentary threshold requirement specified in the election law. They come to the Constitutional Court to request a judicial review on the threshold requirement and plead the Court to revoke the requirement. Meanwhile, civil society groups, which are not the direct participants of the election, will also utilize the medium provided by the Constitutional Court to challenge various provisions in the election law to create a more democratic electoral system. This study concludes that the Constitutional Court is seen as the guarding of constitutional law enforcement institutions and a power relations arena where different political actors strive to realize their political interests or agenda on election laws.